Predisposing factor, impactful adjunctive treatment or unfavorable prognostic marker: a meta-analysis on the elusive role of dexamethasone for Listeria monocytogenes meningitis - Alberto Enrico Maraolo; Maria Mazzitelli (Journal of Infection in Developing Countries)
Introduction: There are no randomized controlled trials to inform the choice of using adjunctive dexamethasone (AD) against Listeria monocytogenes meningitis (LMM) and data from observational studies are pretty conflicting.